OUTCOME OF SUTURELESS MANUAL EXTRA CAPSULAR CATARACT EXTRACTION - Zaman, Mir; Shah, Ashfaq Ali; Hussain, Mahfooz; Babar, Tariq Farooq; Marwat, Muhammad Tariq Khan; Dawar, Sanaullah (Journal of Ayub Medical College Abbottabad, 2009)
Background: Cataract surgery is constantly evolving. Purpose of this study was two folds: to estimate visual outcome and evaluate safety and efficacy of sutureless manual extra-capsular cataract extraction. Methods: This was a prospective, interventional case series, using sutureless manual extra capsular cataract surgery technique from June 2004 to January 2007 at Khyber Institute of Ophthalmic Medical Sciences, Hayatabad Medical Complex Peshawar. Patients included in the study were those having operable cataracts. All those having corneal co-morbidities extensive enough to block visualisation of posterior segment details, chronic adenexal diseases, long standing glaucoma, advanced diabetic eye disease and retinal detachment evident on B-Scan ultrasonography were excluded from the study. After thorough examination and investigation all the patients were operated upon by a single experienced surgeon using the same technique. Their visual outcome was analysed. The patients were followed for a period of six weeks. Results: A total of 1500 cataract surgeries were carried out, of which 1211 (80.74%) patients completed six weeks of follow up. Seven hundred and fifty seven (62.51%) had an uncorrected good visual acuity (6/6-6/18) on 1st post-op day, 1131 patients (93.40%) had an uncorrected visual acuity of 6/6-6/18 on 6th week follow up. Mean surgically induced astigmatism at 6 weeks was 0.3 dioptres. Conclusion: Sutureless manual extra capsular cataract surgery is a safe and effective technique. It offers faster wound healing and quick rehabilitation of cataract patients at any level of community eye care setting. Keywords: Sutureless cataract extraction, visual outcome, astigmatism.